2011
DOI: 10.1111/j.1741-3737.2010.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

If Momma Ain't Happy: Explaining Declines in Marital Satisfaction Among New Mothers

Abstract: This study tests competing explanations for the link between the transition to motherhood and declines in wives' marital satisfaction. Using data from the first and second waves of the National Survey of Families and Households (N = 569), we found that new mothers' marital satisfaction declines could be attributed to reductions in wives' quality time spent with their husbands and to increases in perceptions of unfairness in housework. Family role traditionalization in the wake of the birth of a child did not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
160
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(181 citation statements)
references
References 34 publications
15
160
1
5
Order By: Relevance
“…An abundant body of research concluded that the presence of children at home reduces relationship/marital happiness and satisfaction (Brown & Booth, 1996;Brown, Sanchez, Nock, & Wright, 2006;Dew & Wilcox, 2011;Doss, Rhoades, Stanley, & Markman, 2009;Glenn & McLanahan, 1982;Lawrence, Rothman, Cobb, Rothman, & Bradbury, 2008;Mitnick, Heyman, & Smith Slep, 2009;Sinning & Worner, 2010;Tai et al, 2014;Wendorf, Lucas, Imamoğlu, Weisfeld, & Weisfeld, 2011;Wiik et al, 2009). This reduction in relationship satisfaction has been attributed to the redistribution of roles and responsibilities in the household that follows the birth of a child (Claxton & Perry-Jenkins, 2008;Dew & Wilcox, 2011). This seems to be especially true for women engaged in full-time employment, who report lower levels of wellbeing compared to working fathers (Nomaguchi, Milkie, & Bianchi, 2005).…”
Section: Couple Characteristics Influencing Relationship Satisfactionmentioning
confidence: 99%
“…An abundant body of research concluded that the presence of children at home reduces relationship/marital happiness and satisfaction (Brown & Booth, 1996;Brown, Sanchez, Nock, & Wright, 2006;Dew & Wilcox, 2011;Doss, Rhoades, Stanley, & Markman, 2009;Glenn & McLanahan, 1982;Lawrence, Rothman, Cobb, Rothman, & Bradbury, 2008;Mitnick, Heyman, & Smith Slep, 2009;Sinning & Worner, 2010;Tai et al, 2014;Wendorf, Lucas, Imamoğlu, Weisfeld, & Weisfeld, 2011;Wiik et al, 2009). This reduction in relationship satisfaction has been attributed to the redistribution of roles and responsibilities in the household that follows the birth of a child (Claxton & Perry-Jenkins, 2008;Dew & Wilcox, 2011). This seems to be especially true for women engaged in full-time employment, who report lower levels of wellbeing compared to working fathers (Nomaguchi, Milkie, & Bianchi, 2005).…”
Section: Couple Characteristics Influencing Relationship Satisfactionmentioning
confidence: 99%
“…When women feel satisfied with the division of labor, they are more inclined to report higher marital quality (Dew & Wilcox, 2011;Grote et al, 2002;Wilcox & Nock, 2006). Thus, satisfaction with the division of labor links the actual division of labor and women's marital quality.…”
Section: Linking Family Work and Marital Quality: Satisfaction With Fmentioning
confidence: 99%
“…The presence of children is often attached to responsibilities and pressures of care that are put on women. Uneven distribution of care and domestic chores prompts declines in women's satisfaction, as opposed to time with children (Dew and Wilcox, 2011). Women may enjoy spending more time together in the presence of both the partner and the children because caring responsibilities might be distributed more evenly when their partners are present during activities (Sullivan, Billari, & Altintas, 2014).…”
Section: Work Constraints and Time Spent With Family Membersmentioning
confidence: 99%